Integrative review of literature: nursing care to aged people with HIV - Arayana Gomes da Silva; Viviane Siqueira Cavalcanti; Tâmyssa Simões dos Santos; Gabriela Rodrigues Bragagnollo; Karen da Silva Santos; Ivanilde Miciele da Silva Santos; Kristiana Cerqueira Mousinho; Cinira Magali Fortuna
ABSTRACT Objective: To identify evidences in scientific Brazilian literature on nursing care to aged people with HIV. Method: Integrative review of literature from databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Eletronic Library Online (SciELO), Cochrane and the Nursing Database (BDENF). The applied inclusion criteria were publications that were fully available from 2001 to 2015 and answered to the guiding question of this study. Results: We included 13 studies; and the categories that allowed a better presentation of the scientific evidence on nursing care to aged people with HIV carrier were: Epidemiological profile, perceptions and experiences of aged people with HIV and nursing care to aged people with HIV. Conclusion: The studies address nursing care from a clinic that follows NANDA diagnoses of strong individualizing approach and low consideration of social aspects.